(untitled) - Stallings, William (UpperSadddle River, NJ, 2000)
Provides a clear and comprehensive survey of the whole field of data communications and a tutorial on leading-edge network technologies and protocols. Offers complete and detailed assessment of critical technical areas in data communications, wide-area networking, local area networking, and protocol design. DLC: Data transmission systems.
Keywords: Data transmission systems,Computer networks,Hệ thống quản lý cơ sở dữ liệu,Mạng máy tính